Pola Asuh Orangtua Pedagang Kaki Lima dalam Penanaman Nilai-Nilai Karakter Anak di Kecamatan Kresek - Lala Sholatiyah; Wasehudin Wasehudin; Wahyu Hidayat; Ilzamuddin Ma’mur (Journal on Education, 2024)
Writing this research aims to: First, to describe the parenting style of parents who work as street vendors, in Kresek District, Tangerang Regency. Second, describes the supporting and hindering factors in instilling character values ​​in children. This research method is descriptive, namely field research using a qualitative approach. The subject of this research consists of six families who are the category of street vendors. Data collection technique; on research instruments such as observation, interviews, and documentation which were then analyzed through four steps, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that out of these six families, different parenting patterns and inculcation of character values ​​were found. First, the democratic parenting style used by Pak Kos and his wife, Mrs. Edah and her husband and Mrs. Iim and Mr. Komar. From the parenting style chosen, the character values ​​that were achieved instilled in their children were independent, responsible, disciplined, caring, and fond of learning. Second, it was different from the parenting method used by Mrs. Siti's family and Pak Mamad tended to permissive parenting. This parenting style eventually forms the personality of a child whose interest in learning is low, irresponsible, cowardly, and less independent, which means that the child's character values ​​have not yet been found. Third, the first mixed authoritarian-democratic parenting style was found in the family of Mrs. less control over himself.